(untitled) (Andamios, Revista de Investigación Social, 2009)
This paper discusses four decades of public initiatives to recover the historic center of Bahia, with its approaches, intervention models and changing emphasis: tourism, political marketing. We expose the old center’s historical process of decay and underscore the lack of sustainability of the programs carried out since 1991. Also, we evidence the double process of evicting marginal population and the housing function of the historic center; and the reappropriation of the place by many Afro-Brazilian groups. In conclusion we criticize imported models of intervention and plead for the development of a Latin-American theory about the requalification of our historic centers, and for searching new solutions based upon our specificities.